ANALISIS YURIDIS TERHADAP KOMPETENSI ABSOLUT PENGADILAN TATA USAHA NEGARA DALAM MENYELESAIKAN SENGKETA PEMECATAN ASN - Ritonga, Joni Sandri; Aulia, Cindy; Inayah, Dea Zulfa; Rahmadani, Mirna Syafitri; Aldi Khoiri, Muhammad; Arifah, Rizka; Ritonga, Sumantri (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study analyzes the absolute competence of the Administrative Court (PTUN) in resolving disputes concerning the dismissal of Civil Servants (ASN) from a juridical perspective. The absolute competence of PTUN represents exclusive authority that cannot be delegated to other judicial institutions. In the context of ASN dismissal, PTUN functions as a forum for resolving disputes arising from final and concrete decisions made by administrative officials. This research aims to identify the boundaries of PTUN's absolute competence in ASN dismissal cases and to examine the relevance and effectiveness of this authority in providing legal protection for ASN. The study adopts a normative juridical approach by analyzing legislation, court decisions, and related legal doctrines. The findings reveal that PTUN plays a significant role in assessing the legality of ASN dismissal decisions. However, the limits of PTUN's absolute competence often spark debates, particularly in disputes involving employment aspects such as disciplinary violations or the implementation of Government Regulation Number 94 of 2021 on Civil Servant Discipline. The study also finds that procedural and substantive irregularities in the dismissal process frequently serve as grounds for annulment by PTUN. Nevertheless, coordination between PTUN and the Civil Service Advisory Board (Badan Pertimbangan ASN) requires strengthening to ensure comprehensive legal protection. In conclusion, PTUN's absolute competence in ASN dismissal disputes remains relevant but necessitates regulatory harmonization to avoid overlapping authority and to ensure substantive justice for ASN.